Knee Extensor Strength Prediction Formula Using Modified Aneroid Sphygmomanometer in Healthy Female Adults - Erik Setiawan; Marietta Shanti Prananta; Novitri Novitri (International Journal of Integrated Health Sciences, 2018)
Objective: To discover isometric knee extensor muscle strength prediction formula using hand-held dynamometer (HHD) through the use of modified aneroid sphygmomanometer (MAS). Isometric knee extensor muscle strength examination is required to diagnose and evaluate the treatment of quadriceps femoris weakness.Methods: This was a quantitative observational and correlational analysis study with cross-sectional design. Isometric knee extensor muscle strength was measured using HHD and MAS with 60o knee flexion in sitting position. Correlation tests were performed to investigate the correlation between HHD, MAS, and other variables. Regression test was carried out to analyze knee extensor strength regression using HHD through MAS.Results: TSubjects enrolled were 25 healthy females aged 23–52 years old. The correlation between HHD and MAS was significant while age, body weight, body height, and body mass index (BMI) did not show correlation with HHD and MAS. The isometric knee extensor muscle strength using HHD could be predicted by formula = 0.1041xMAS.Conclusions: Isometric knee extensor muscle strength measured using HHD strongly correlates with that of using MAS with 60o knee flexion in sitting position and can be predicted from measurement values of MAS. The formula is only suitable for females.Keywords: Hand-held dynamometer, knee extensor, prediction formula, sphygmomanometer DOI: 10.15850/ijihs.v6n1.1103